In-Home Observations Are a Useful Tool to Assess the Household Enabling Environment for Child Nutrition in Burkina Faso and Sierra Leone - Schmall, Alexandria (Curr Dev Nutr, 2021)
OBJECTIVES: Two field studies assessed the effectiveness and cost-effectiveness of specialized nutritious foods (SNF) to prevent and treat malnutrition among children 6–24 months old in Burkina Faso and 6–59 months old in Sierra Leone. In-home observations (IHO) were conducted to understand household use of SNFs. The IHO data are unique, as local enumerators directly observed caregiver behaviors that would otherwise be provided by self-report. In this study, we examined household factors that may influence child nutrition, including child feeding, care, and hygiene practices among caregivers, and sanitary conditions of the home environment. METHODS: Local enumerators conducted 3–5-day IHO among a subset of 321 and 176 beneficiary households in Sierra Leone and Burkina Faso, respectively. Using time-stamped checklists and detailed observation notes, they recorded household activities, focused on feeding and care of beneficiary children. Detailed enumerator notes were analyzed using qualitative content analysis. RESULTS: Similar trends emerged in both countries. Poor hand-washing and food hygiene practices were common among caregivers; children consumed poor quality, starchy diets; children were most often cared for by their mothers and other adult, female relatives. Child feeding during illness was poor, and child mouthing of unsanitary household objects was common. In Burkina Faso, domestic animals were frequently present in the courtyard and near children during meals. CONCLUSIONS: Future nutrition interventions may consider approaches that address multiple household factors that contribute to an enabling environment for child nutrition. Further, considering the feasibility of field application, the IHO method may be used in future nutrition programs to provide information beyond what could be obtained accurately from caregiver self report, and thus help inform nutrition behavior change strategies. FUNDING SOURCES: Support for this research was provided by the USAID Bureau for Humanitarian Assistance.